2013
DOI: 10.3389/fncel.2012.00070
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endogenous neural stem/progenitor cells for neural repair—factors that promote neurogenesis and gliogenesis in the normal and damaged brain

Abstract: Neural stem/precursor cells in the adult brain reside in the subventricular zone (SVZ) of the lateral ventricles and the subgranular zone (SGZ) of the dentate gyrus in the hippocampus. These cells primarily generate neuroblasts that normally migrate to the olfactory bulb (OB) and the dentate granule cell layer respectively. Following brain damage, such as traumatic brain injury, ischemic stroke or in degenerative disease models, neural precursor cells from the SVZ in particular, can migrate from their normal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
102
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 272 publications
(302 reference statements)
0
102
0
Order By: Relevance
“…Additionally, although a number of cellular mechanisms involved in the regulation of postnatal neurogenesis in neurogenic brain regions have been identified (16), the specific factors that may induce the differentiation of immature neurons in nonneurogenic regions are largely unknown. Among general factors that impact cell proliferation in neurogenic regions (17), focal brain lesions may also influence the differentiation of immature neurons in the postnatal monkey amygdala.…”
mentioning
confidence: 99%
“…Additionally, although a number of cellular mechanisms involved in the regulation of postnatal neurogenesis in neurogenic brain regions have been identified (16), the specific factors that may induce the differentiation of immature neurons in nonneurogenic regions are largely unknown. Among general factors that impact cell proliferation in neurogenic regions (17), focal brain lesions may also influence the differentiation of immature neurons in the postnatal monkey amygdala.…”
mentioning
confidence: 99%
“…23 While the regulation of ischemia-induced neurogenesis is poorly understood, various growth factors are known to be implicated in precursor cell proliferation in the subventricular zone as well as in chemotaxis toward the sites of injury and survival of neuroblasts in the ischemic border zone. 24 In this context, the ability of HUCB MNC to increase local growth factor levels after stroke, either by direct secretion or by inducing host expression, 9 is supposed to be a major mediator of the reported beneficial effects. In this study, we found a rapid increase of endogenous BDNF, nerve growth factor, and basic fibroblast growth factor mRNA after the ischemic injury; however, HUCB MNC treatment did not further augment these levels within 48 hours after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Specific functions that rely upon neurogenesis include new learning for the hippocampus [69], and rich olfactory sensory experience for the olfactory bulb [70]. As this occurs regularly in an activity-dependent manner already, it stands to reason that neuronal precursors transplanted into these regions would be more likely to receive signals encouraging their incorporation into either the hippocampus or the olfactory bulb, and in fact, this seems to be the case [71,72]. Yet in other regions such as the striatum (the main input structure of the basal ganglia), the capacity of endogenous neuronal progenitors to become neurons seems reduced compared to exogenous transplantations [73].…”
Section: Adaptation Of Endogenous Host Tissue To Neural Transplantationmentioning
confidence: 99%